2017
DOI: 10.3390/nu9121292
|View full text |Cite|
|
Sign up to set email alerts
|

Estimating Free and Added Sugar Intakes in New Zealand

Abstract: The reduction of free or added sugar intake (sugars added to food and drinks as a sweetener) is almost universally recommended to reduce the risk of obesity-related diseases and dental caries. The World Health Organisation recommends intakes of free sugars of less than 10% of energy intake. However, estimating and monitoring intakes at the population level is challenging because free sugars cannot be analytically distinguished from naturally occurring sugars and most national food composition databases do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 14 publications
(17 reference statements)
2
38
0
Order By: Relevance
“…These results are similar to the figures presented in a review [26] of added sugar consumption reported in nine nutrition surveys across the world (6% TE to 19% TE in people over 4 years old). In the present study, the intake of free sugars as defined by the WHO and the SACN ranged from 9% TE to 13% TE, similar to the free sugar intake reported in the Dutch National Food Consumption Survey 2007-2010 [16], in the New Zealand Adult Nutrition Survey 2008/09 [17] and in Swiss National Nutrition Survey (2014-2015) [27] which were, on average, 14% TE in 7-69 years old, 11% TE in 15-71 years old and 11% TE in 18-75 years old, retrospectively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are similar to the figures presented in a review [26] of added sugar consumption reported in nine nutrition surveys across the world (6% TE to 19% TE in people over 4 years old). In the present study, the intake of free sugars as defined by the WHO and the SACN ranged from 9% TE to 13% TE, similar to the free sugar intake reported in the Dutch National Food Consumption Survey 2007-2010 [16], in the New Zealand Adult Nutrition Survey 2008/09 [17] and in Swiss National Nutrition Survey (2014-2015) [27] which were, on average, 14% TE in 7-69 years old, 11% TE in 15-71 years old and 11% TE in 18-75 years old, retrospectively.…”
Section: Discussionsupporting
confidence: 83%
“…The measurement of added and free sugar content of foods and drinks is a challenge as there is no laboratory based analytical method or biomarker [14] that can objectively measure these sugars due to the difficulty in distinguishing intrinsic sugars from extrinsic sugars [15,16]. There are some methods [15,17] which estimate the added and free sugars content of foods in a systematic way from intake data. However, these are mostly specific to a single definition such as added sugar or free sugar only and are difficult to use more flexibly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…"Free sugars include monosaccharides and disaccharides added to foods and beverages by the manufacturer, cook or consumer, and sugars naturally present in honey, syrups, fruit juices, and fruit juice concentrates [36]." Since free sugars are not found in the South African Food Composition Tables, we used the method used to calculate free sugars in New Zealand [40].…”
Section: Data Analysesmentioning
confidence: 99%
“…An added complexity is that it is not possible to distinguish naturally occurring sugars from added sugars from an analytical standpoint [ 19 , 20 ]. There are various indirect methods for estimating the added sugar and free sugar content of food and drinks [ 19 , 20 , 21 , 22 , 23 , 24 ], however, all these methods have limitations, mainly due to the level of subjectivity and general assumptions involved in decision making (for example all savory breads are sugar-free). In addition, these methods are mostly specific to a single definition of sugars, and thus may not be able to adapt readily to accommodate any changes in the definition.…”
Section: Introductionmentioning
confidence: 99%